2014
DOI: 10.1007/s00423-013-1156-4
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative adverse events during laparoscopic colorectal resection—better laparoscopic treatment but unchanged incidence. Lessons learnt from a Swiss multi-institutional analysis of 3,928 patients

Abstract: Intraoperative surgical complications and adverse events in laparoscopic colorectal resections did not change significantly over time and are associated with an increased postoperative morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 29 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…Our findings further showed that factors such as the type of procedure, pre-therapeutic and intraoperative complications, gender, preoperative chemotherapy, staging, and hospital category predispose a patient to postoperative complications. Previous studies supported this (34,35,38,39). If these factors influencing postoperative complications in patients undergoing CRC surgery are identified and controlled, the impact of this variable on LOS may decline drastically, and the overall post-surgical quality of life of the patients may be improved.…”
Section: Discussionmentioning
confidence: 67%
“…Our findings further showed that factors such as the type of procedure, pre-therapeutic and intraoperative complications, gender, preoperative chemotherapy, staging, and hospital category predispose a patient to postoperative complications. Previous studies supported this (34,35,38,39). If these factors influencing postoperative complications in patients undergoing CRC surgery are identified and controlled, the impact of this variable on LOS may decline drastically, and the overall post-surgical quality of life of the patients may be improved.…”
Section: Discussionmentioning
confidence: 67%
“…The most frequent complication was bleeding (3.6%), followed by bladder injury, ureter injury, and perforation, with a percentage of 1.2% for each. A previous study reported a 4.1% IOC consisting of bleeding (1.6%) and solid organ lesions (1.6%) [ 16 ]. Furthermore, a previous study done in Switzerland reported closer rates of 7.4% IOC, with bowel injury being the most common IOC with a percentage of 32.1% [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The current study captured a higher yield of patient impact events than previously reported in the literature. 28,29 With voluntary reporting, only 6% of hospital-based adverse drug events detected by direct observation were reported, even in the setting of severe patient harm. 30 In the current study, 12.9% (22 of 171) of nonroutine events with patient impact event ratings were deemed to be "drug related."…”
Section: Patient Impact Eventsmentioning
confidence: 99%